354 Evaluation of the New AJCC Tumor (T) Stage in Patients With Pancreatic Ductal Adenocarcinoma. (11th January 2018) - Rubenstein, Wesley; Lin, Grace; Valasek, Mark; Tipps, Ann; Vavinskaya, Vera; Hosseini, Mojgan
Abstract: Background: The new exocrine pancreas staging system by the American Joint Committee for Cancer (AJCC, Eighth edition) for pancreatic ductal adenocarcinoma (PDAC) is entirely size-based. Tumors are classified as pT1, ≤2 cm (pT1a, ≤0.5 cm; pT1b, >0.5 cm and <1 cm; pT1c, 1–2 cm), pT2, >2 cm and ≤4 cm, and pT3, >4 cm. The previous stage T3, tumor extension beyond the pancreas but without involvement of the celiac axis or the superior mesenteric artery, does not exist anymore. There is no change in stage T4. Design: We retrospectively analyzed 79 cases of pancreatic ductal adenocarcinoma (with or without neoadjuvant therapy) from 2010 through 2017 and restaged them based on the new AJCC, Eighth edition, system. Results: We retrospectively analyzed 79 cases (44 women and 35 men; mean age of 65 years). Twenty-four cases were post neoadjuvant treatment. Reclassifying the cases by AJCC, Eighth edition, resulted in restaging of 57 cases (72%): 45 of the cases (57%) were downstaged, six cases (7.6%) were upstaged, and there was no change in the staging of 28 cases (35.5%). A total of seven patients were upstaged from T2 to T3, two of whom are deceased at the time of this study. A total of 45 cases were downstaged. The majority (39 cases, 86.6%) was downstaged from T3 to T2, 18 (40%) of whom were deceased at the time of the study. Conclusions: Our study shows how AJCC, Eighth edition, affects the staging in pancreatic ductal carcinomas. Large-scale clinical studies are needed to validate the new system and correlate it with patient outcomes.